The Role of Chinese Language Learners' Academic Resilience and Mindfulness in Their Engagement - Liu, Wei; Gao, Yonggang; Gan, Lu; Wu, Jinwen (Frontiers in Psychology, 2022)
One of the growing area of interest in the educational area is student engagement which is the major construct of positive psychology (PP) vital in growing energetic, innovative, and pleasurable learning, but unluckily, all students are not engaged in terms of cognition, emotion, and behavior in learning. Another concept in the PP literature is resilience which emphasizes institutes’ and people’s powers and self-constraint to conform to accidental conditions. Furthermore, mindfulness as a significant term in PP has critical benefits such as improving working memory, improving wellbeing, and lowering tension. Considering the importance of mindfulness and engagement in academic environments and that such a notion in foreign language learning is neglected, the current study attempts to inspect the effect of mindfulness and resilience on the engagement of Chinese foreign language students. To meet this objective, 1693 EFL learners participated in this study. They responded to the mindfulness scale, resilience scale, and engagement questionnaire. Subsequently, the Spearman Rho test was exploited to shed light on probable relationships. The findings indicated that there was a significant correlation among the variable of the study. Moreover, a linear multiple regression analysis was run to examine the predictor roles of mindfulness and resilience in learners’ engagement. The findings revealed that both mindfulness and resilience are positive and reliable predictors of engagement. In a nutshell, the central position of resilience and mindfulness in language learning was verified, and based on the findings; a few suggestions are made considering the results of the research.